Characterization of magnetorheological brake for speed control application - Zainordin, Ahmad Zaifazlin (2014)
Magnetorheological (MR) brake is one of the brake-by-wire technologies which is developed using MR fluid by immersing it in MR brake mechanism. This study deals with the development of MR brake in order to characterize and implement control system for shaft speed application. It began from the literature review of previous study on MR brake and continue the development of MR brake with a test rig. The MR brake was characterized at various current in order to obtain the brake torque during braking. In addition, the MR brake was also characterized at various loads to study the response such as angular velocity, brake torque and displacement responses. Next, the mathematical model of MR brake was simulated and verified with the experimental data. Then, the study continues with performance evaluation of shaft speed control using MR brake. There are two controllers implemented and compared in order to study controller performance under the influence of loads. Two types of controllers, On-Off and PID have been implemented with MR Brake. According to the performance of both controllers, PID controller shows better performance compare to On-Off controller.